2017
DOI: 10.17265/1934-7391/2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Helicobacter pylori Infection and Related Gastric Pathologies in Moroccan Population

Abstract: Abstract:Helicobacter pylori (H. pylori) colonize the gastric mucosa of 50% of the world's population. This infection is closely associated with the development of peptic ulcer disease and gastric cancer. The present study was conducted to assess the prevalence of H. pylori infection in Moroccan population and the risk to develop gastric precancerous lesions and gastric cancer. Totally, 298 patients were enrolled, 68 of asymptomatic subjects and 230 of patients with gastric diseases. Histological examination w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…In our series, the prevalence of H. pylori in symptomatic adults was 75.3 and 82.5% by histological examination and PCR, respectively. This prevalence is consistent with the general prevalence in Africa which is 70% and the prevalence found in Morocco which was 92.6% in asymptomatic people and 89.6% in people suffering from gastric disorders [ 1 , 15 ] and in Tunisia where the prevalence was 87.7% in symptomatic patients in 2005 and 63.7% in 2022 in a multicenter Tunisian study [ 16 ]. Our study involved patients who fulfilled the indications for H. pylori testing set out in the Maastricht VI consensus [ 2 ].…”
Section: Discussionsupporting
confidence: 89%
“…In our series, the prevalence of H. pylori in symptomatic adults was 75.3 and 82.5% by histological examination and PCR, respectively. This prevalence is consistent with the general prevalence in Africa which is 70% and the prevalence found in Morocco which was 92.6% in asymptomatic people and 89.6% in people suffering from gastric disorders [ 1 , 15 ] and in Tunisia where the prevalence was 87.7% in symptomatic patients in 2005 and 63.7% in 2022 in a multicenter Tunisian study [ 16 ]. Our study involved patients who fulfilled the indications for H. pylori testing set out in the Maastricht VI consensus [ 2 ].…”
Section: Discussionsupporting
confidence: 89%
“…24 We discovered that the detection rate of gastric lesions was higher in the H. pylori-positive population compared to the H. pylori-negative population, consistent with previous studies, whether based on serological testing or UBT to determine H. pylori infection. [25][26][27] Additionally, a 16-year follow-up study involving patients with persistent H. pylori infection found that long-term infection was related to the development of precancerous lesions. 28 Previous studies showed that the infection has different roles in reducing the risk of esophageal adenocarcinoma and esophageal squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the authors of this metaanalysis concluded that Nigeria has the highest H. pylori prevalence worldwide, at 87.7%. In Southern Africa, Walker www.videleaf.com et al [67] reported an overall prevalence of 75%, whereas, in Northern Africa, Bounder et al [68] found a prevalence of 92.6% in asymptomatic Moroccans and 89.6% in patients complaining of gastric symptoms regardless of age. Another study performed in Egypt revealed a lower prevalence in the general population of only 54.4% [69].…”
Section: H Pylori Peculiarities In Africamentioning
confidence: 99%
“…In terms of diagnostic methods, most of the reported studies in Africa used serology testing, which might not be the most accurate mirror of the real prevalence in this population [78]. For example, most of the studies in Libia relied on serological tests for diagnosing H. pylori infection [68][69][70]. Nevertheless, in areas like Algeria, Tunisia, West, East, or Central Africa, studies also reported the use of more accurate methods such as a urea breath test, stool antigen, rapid urease test, or histological exam based on upper digestive endoscopy collected gastric biopsies and their combination [79][80][81].…”
Section: H Pylori Peculiarities In Africamentioning
confidence: 99%
See 1 more Smart Citation